«Quattro animaluzzi, che vivono in su un pugno di fango». Una lettura ecopessimista delle Operette morali - Tognocchi, Luca (Rivista Internazionale di Studi Leopardiani, 2023)
A link between ecology and pessimism has emerged strongly in recent years, in philosophers such as Thacker, Ligotti, and Morton, or even in the reflections carried out on the writings of eco-terrorist Theodore Kaczynski, known as the Unabomber. The intent of this proposal is to apply the categories and theories of pessimistic thought on the environment to some of the texts in the Operette, such as Dialogo della Natura e un Islandese, Il Copernico, or Dialogo di un Folletto e di uno Gnomo.